Medicalizing Ethnicity : The Construction of Latino Identity in a Psychiatric Setting - Santiago-Irizarry, Vilma (Book collections on Project MUSE., 2001)
In Medicalizing Ethnicity, Vilma Santiago-Irizarry shows how commendable intentions can produce unintended consequences. Santiago-Irizarry conducted ethnographic fieldwork in three bilingual, bicultural psychiatric programs for Latino patients at public mental health facilities in New York City. The introduction of "cultural sensitivity" in mental health clinics, she concludes, led doctors to construct essentialized, composite versions of Latino ethnicity in their drive to treat mental illness with sensitivity. The author demonstrates that stressing Latino differences when dealing with patients resulted not in empowerment, as intended, but in the reassertion of Anglo-American standards of behavior in the guise of psychiatric categories by which Latino culture was negatively defined. For instance, doctors routinely translated their patients' beliefs in the Latino religious traditions of espiritismo and Santería into psychiatric terms, thus treating these beliefs as pathologies. Interpreting mental health care through the framework of culture and politics has potent effects on the understanding of "normality" toward which such care aspires. At the core of Medicalizing Ethnicity is the very definition of multiculturalism used by a variety of institutional settings in an attempt to mandate equality